Dakwah Dan Ekonomi Kemasyarakatan - Ahmad Taufik; Nurlila Kamsi; Siti Hana; Taufik Mukmin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
The proselytizing used is bilhal i.e. in a natural way. By using deeds or examples as the message. So the message of proselytizing that is an example in the efforts of the community economy is very good and very important to be understood in a comprehensive manner. This research is qualitative research in the form of field and literature studies. The purpose of proselytizing is as an answer to challenges and social problems (solutive). As for the problem of solutions to the dahwah and economy of the first society, in modern society must have a good socialization relationship related to morals in oneself, society, family and nation. Second, the economy of society. then the solution in this challenge is the need for humans with a high work ethic, high discipline and having a forum for the Amil Zakat and Alms Agency as an effort to optimize the improvement of Muslim understanding to share with others.